Remarks at the Venice Climate Conference - Malpass, David (World Bank, Washington, DC, 2021)
World Bank Group President David Malpass spoke about the Coronavirus (COVID-19) pandemic and the devastating economic losses. The World Bank Group is providing maximum support to developing economies to respond to the crisis, and working to help them recover in ways that will be sustainable, greener and more prosperous. The Bank Group financing is aligning with the Paris Agreement goals. The Group will help client countries in their efforts to develop and implement their Nationally Determined Contributions and Long-Term Strategies. The Group is enhancing core analytical products such as the recently launched Country Climate and Development Reports and a facility on climate-informed Public Expenditure Reviews. He expressed the need for diagnostics, and a data-driven approach to help prioritize action. There is also need for a parallel effort to protect our natural capital and biodiversity, so that solutions work for people and the planet. IFC and MIGA that are mobilizing private sector financing and helping companies lower their emissions.